Melampaui rumus: analisis kesiapan kognitif siswa dalam menghadapi soal literasi matematis tipe PISA - Nurjanah, Intan; Hendriana, Benny (Universitas Muhammadiyah Prof. DR. HAMKA, 2025)
This study analyzes the mathematical literacy level of junior high school students based on Bloom's Taxonomy cognitive levels, motivated by the low achievement of Indonesian students in PISA 2023. Using a descriptive qualitative method, the study involved 30 seventh-grade students of SMPIT Al-Arobi through essay tests and structured interviews. The results showed 43% of students at the low level (D), 7% at very low (E), and only 20% reached the excellent level (A). In-depth analysis of three subjects (BL, AAB, FT) revealed disparities in ability: BL (level C5-C6) is capable of complex analysis and mathematical modeling, while AAB (C3) and FT (C1-C2) are limited to procedural applications and basic understanding. These findings confirm that the procedural learning approach and the lack of contextual problem practice are the main inhibiting factors. This study provides an important contribution in the development of complex problem-based mathematics learning models to improve students' Higher-Order Thinking Skills (HOTS). Penelitian ini menganalisis tingkat literasi matematis siswa SMP berdasarkan level kognitif Taksonomi Bloom, dilatarbelakangi oleh rendahnya capaian siswa Indonesia dalam PISA 2023. Menggunakan metode kualitatif deskriptif, penelitian melibatkan 30 siswa kelas VII SMPIT Al-Arobi melalui tes esai dan wawancara terstruktur. Hasil menunjukkan 43% siswa pada level rendah (D), 7% sangat rendah (E), dan hanya 20% mencapai level sangat baik (A). Analisis mendalam terhadap tiga subjek (BL, AAB, FT) mengungkap disparitas kemampuan: BL (level C5-C6) mampu analisis kompleks dan pemodelan matematis, sementara AAB (C3) dan FT (C1-C2) terbatas pada aplikasi prosedural dan pemahaman dasar. Temuan ini mengkonfirmasi bahwa pendekatan pembelajaran prosedural dan kurangnya latihan soal kontekstual menjadi faktor penghambat utama. Penelitian memberikan kontribusi penting dalam pengembangan model pembelajaran matematika berbasis masalah kompleks untuk meningkatkan Higher-Order Thinking Skills (HOTS) siswa.